Impacting teachers' and students' spiritual well‐being - Fisher, J.W. (2008)
Spiritual well‐being (SWB) is reflected in the quality of relationships that people have with themselves, others, environment and/or God. This paper ties together several studies of SWB among teachers and students in primary and secondary, state, Catholic, other Christian, and independent schools in Victoria, Australia. Teachers' lived experiences have greatest impact on their perceptions of help provided by schools for students' SWB. Factors other than teachers contribute most to students' SWB. As well as presenting an overview of key supports for students' SWB this paper reports ways in which spiritual dissonance can be identified. These findings could be used to lay a foundation for further support in nurturing the total well‐being of staff and students in schools.
Keywords: Shalom; help for spiritual well‐being; spiritual dissonance